Biochemical and immunological effects of ionizing radiation in radiology staff members - Serhatlioglu, Selami; Ogur, Erkin; Ozan, A Tevfik; Gürsu, Ferit; Gödekmerdan, Ahmet; Ayar, Ahmet (My University, 2004)
PURPOSE: This study aimed to investigate the influence of occupational exposures to long term low-dose ionizing radiation on blood biochemistry and immunity levels of the radiology staff. MATERIALS AND METHODS: Fifty-one subjects, aged between 21-57 years (30.06+/-7.02 years), working in the department of radiology were enrolled to this study. Twenty-five subjects (49.1%) were female and 26 (50.9%) were male. Control group consisted of 40 healthy non-smoking subjects aged between 20-60 years (mean 31.5+/-5.75) who had never been exposed to radiation; 19 (47.5%) of these were female and 21 (52.5%) male. Venous blood samples were obtained from the radiology staff and control group and immunological and biochemical analysis of samples were performed. RESULTS: CD4+ T-lymphocyte ratio, and serum total IgA, IgG, IgM and C3, C4 levels were lower in the radiology staff compared to the controls. Serum triglycerides and paraoxonase activities were increased in the radiology staff (p<0.05). CONCLUSION: In radiology workers exposed to long-term low-dose ionizing radiation, levels of the CD4+ T lymphocytes, total immunoglobulins (IgA, IgG, IgM), C3 and C4 levels were lower, while serum trygliceride levels and paraoxonase activities were significantly higher (p<0.05). IgA and IgM levels of smoker radiology workers were significantly lower than non-smoker radiology workers (p<0.05). Since the staff members of department of radiology are vulnerable to the side effects in parallel to the dose of radiation being exposed, we think that in addition to avoiding radiation as much as possible, they should have periodical blood biochemistry and immune function tests.
Iyonizan radyasyonun radyoloji çalişanlarinin bagişiklik düzeyleri ve kan biyokimyasi üzerine etkileri.
Keywords: Adult; Case-Control Studies; CD4 Lymphocyte Count; Female; Humans; Immunoglobulins; Male; Middle Aged; Occupational Exposure; Personnel, Hospital; Radiation Injuries; Radiation, Ionizing; Radiology Department, Hospital; T-Lymphocytes; Turkey; immunoglobulin; adult; article; blood; case control study; CD4 lymphocyte count; drug effect; female; hospital personnel; human; ionizing radiation; male; middle aged; occupational exposure; radiation exposure; radiation injury; radiology department; T lymphocyte; Turkey (republic)